Performance Of Multilevel Inverters For Harmonic Reduction In Dynamic Voltage Restorer Application - Nordin, Norsyuhada (2018)
Multilevel inverters are known for their intial usage in high-voltage and high-power applications.This thesis presents the analysis and design of the Three-Phase Cascaded H-Bridge Multilevel Inverters (CHB-MLI) for three and five levels based on Newton-Raphson technique for harmonic reduction in Dynamic Voltage Restorer (DVR) application.The performance of the inverter outputs to reduce harmonics is crucial for DVR applications.Two DC sources were applied for two types of CHB-MLI.These types of inverters used Newton-Raphson method as their controllers.The main aim of this thesis is to design, model,construct,and conduct laboratory testing upon CHB-MLI of a three and five levels prototype for DVR application.The design of suitable multilevel inverters is very important for DVR purposes,so that the AC output voltage waveforms of the inverters have low content of harmonics during energy conversion process from DC to AC of the proposed inverters.The Digital Signal Processing (DSP) TMS320F2812 was used as a tool in order to create the coding based on the Newton-Raphson technique controller.The coding was developed,and then stored into the Digital Signal Processing (DSP) TMS320F2812 for output processing of the waveform of the inverters.The proposed controller using Newton-Raphson technique was applied to both three and five level of CHB-MLI.The optimization of this system has managed to reduce the harmonic contents of the inverters output.The performance of the developed prototype was tested using source codes of the programming for optimization technique.The experimental results of the developed prototype for both three and five levels were monitored and analysed.In addition,the performance of the proposed system was compared between simulation and experimental results for the optimization technique.The simulation and experimental results had shown the effectiveness of the proposed system in reducing harmonic.The waveforms in term of current and voltage were smooth and contain low contents of harmonic.Types of waveforms for five level of CHB-MLI which were more suitable to be used in the DVR applications.